Spectroscopy of high-Z ions as a way to understanding the nature of Cas A knots and intergalactic shocks - Docenko, Dmitrijs (My University, 2008)
The goal of the studies comprising this thesis is a survey of prospective spectroscopical methods of highly-charged ion observations from hot astrophysical plasmas that have not been widely studied before. The first main task that one needs to carry out in this case is a review of different types of spectral lines and matching types of astrophysical objects. This review is then followed by the development of the theoretical description and determination of the best observable parameters in the promising direction and application of the method to the specific objects. Two results of such study (combinations of spectral line type and object type) are presented in the thesis. The hyperfine structure lines of highly-ionized metal atoms (primarily the line of 14N VII at 5.652 mm) are shown to be observable with modern radio telescopes.The astrophysical objects responsible for appearance of these lines either in emission or in absorption are hot interstellar medium in the Galaxy and other galaxies, hot intracluster medium in clusters of galaxies, supernova remnants, gas around quasars and the warm-hot intergalactic medium, being the most interesting object for the application of the proposed method. The highly-ionized metal recombination lines in the optical and near-infrared ranges constitute another promising result of our studies. We have shown that the lines of this previously unstudied type should be strong enough to be observable even in moderate time on the modern ground-based optical telescopes from the dense knots of ejecta of the young Galactic supernova remnant Cassiopeia A. Such prospective observations will allow to identify all abundant ions present in the ejecta being crossed by the reverse shock wave of the supernova explosion, thus increasing our knowledge both on the ejecta composition and details of the shock wave interaction with the metal-dominated dense clouds. In the course of the work, it was realized that the physical conditions in the emitting regions of these dense ejecta clouds (so-called fast-moving knots) of Cassiopeia A and other young oxygen-dominated supernova remnants are rather unconstrained with predictions of different models for the line intensities varying by orders of magnitude. To make better estimates of these conditions from the existing data, we have utilized the archival observations of ISO and Spitzer space observatories to determine the diagnostic fine-structure line ratios. Analysis of this observational data set has resulted in understanding of relative importances of various processes proposed in different theoretical models, as well as in determination of physical parameters in some of previously observationally unexplored regions of the fast-moving knots. This study is also included in the thesis.
Disertācija izstrādāta un aizstāvēta Minhenē.
Keywords: Spektroskopija; Spectroscopy